Solidarity Amidst Hardship: Female Animal Narratives in The Help - Du Yue (SHS Web of Conferences)
The Help tells the story of racial segregation in Jackson, Mississippi, in the early 1960s. In the novel, animals symbolize the marginalized existence of white and black women under male and racial oppression. White women are demeaned in marriage and the workplace, while black women face silence regarding bodily and linguistic rights. This paper, from a feminist and postcolonial perspective, integrates animal criticism to examine the portrayal of animals like cockroaches, bears, and dogs, illustrating the existential dilemma of these women and exploring ways to overcome these challenges. It argues that Stockett depicts both groups’ discourses as ineffective under patriarchy and racism but also highlights the positive aspects of inter-female assistance across racial lines and the inevitable breakdown of racial segregation.